2019
DOI: 10.13057/biodiv/d200519
|View full text |Cite
|
Sign up to set email alerts
|

Effect of phytoremediation on the morpho-anatomical characters of some aquatic macrophytes

Abstract: Abstract. Napaldet JT, Buot Jr. IE, Zafaralla MT, Lit Jr. IL, Sotto RC. 2019. Effect of phytoremediation on the morpho-anatomical characters of some aquatic macrophytes. Biodiversitas 20: 1289-1302. In constructed wetland studies, the effect of pollutants or the phytoremediation set-up on aquatic macrophytes is often not investigated. This literature gap may prove useful in realizing the full phytoremediation potential of aquatic macrophytes. This study was conducted to examine the effect of phytoremediation, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 6 publications
0
3
0
1
Order By: Relevance
“…The aerenchyma of aquatic plant roots experienced a significant increase in heavy metal stress and metaxylem. This condition is an attempt by plants to accumulate heavy metals, so they do not enter further and become toxic to plants (Batool et al 2014;Napaldet et al 2019;Li et al 2023).…”
Section: The Growth Of E Palifoliusmentioning
confidence: 99%
“…The aerenchyma of aquatic plant roots experienced a significant increase in heavy metal stress and metaxylem. This condition is an attempt by plants to accumulate heavy metals, so they do not enter further and become toxic to plants (Batool et al 2014;Napaldet et al 2019;Li et al 2023).…”
Section: The Growth Of E Palifoliusmentioning
confidence: 99%
“…Organic matter evaporates from the stems and leaves through a direct phytovolatilization mechanism or from the soil through root activity called indirect phytovolatilization mechanism (Limmer and Burken 2016;Ekta and Modi 2018). Phytoremediation agents such as A. microphylla absorb components from the environment which are then processed in the tissue metabolism to remove pollutants (Alkorta et al 2004;Tulod et al 2012;Varghese and Jacob 2016;Napaldet et al 2019). Unisah and Akbari (2020) showed that the use of A. microphylla in tofu wastewater treatment reduced 96% of BOD.…”
Section: Biochemical Oxygen Demand (Bod) Reductionmentioning
confidence: 99%
“…Phytoremediation agents such as A. microphylla are more tolerant towards pollutants in the environment because they can absorb components from the environment that are metabolized inside the tissues (Alkorta et al 2004;Tulod et al 2012;Varghese and Jacob 2016;Napaldet et al 2019 ). In this case, A. microphylla can accumulate large amounts of contaminants into the biomass (Arora et al 2006).…”
Section: Sulfides (H2s) Reductionmentioning
confidence: 99%
“…El conocimiento de los caracteres morfoanatómicos de las plantas acuáticas puede revelar adaptaciones al ambiente y manifestar cambios ecológicos de los mismos (Sandulescu et al, 2016). A través de dichos estudios se pueden inferir manifestaciones de estrés o contaminación ambiental; y también permiten detectar el potencial fitorremediador de las plantas nativas, lo que podría derivar en resultados más eficientes en la limpieza de los ambientes contaminados (Wood & McAtamney, 1994;Baruah et al, 2014;Guittonny-Philippe et al, 2015;Napaldet et al, 2019;Olaranont et al, 2020). El uso de rasgos morfo-anatómicos vegetativos puede proporcionarnos información cuantitativa para explicar la ecología de las macrófitas (Dalla-Vecchia et al, 2020).…”
unclassified